Mouth-parts, male and female genitalia as identification tools of Sergentomyia (Sintonius) clydei and phylogenetic relationships - J. K. Kakarsulemankhel (نامه انجمن حشره‌شناسی ایران, 2009)
Sergentomyia (Sintonius) clydei (Sinton) is for the first time recorded from the endemic localities of cutaneous leishmaniasis in Sindh, Punjab and N.W.F province (Pakistan). In view of the published reports about the detection of encephalitis viruses from the species of the genus Sergentomyia Franca & Theodor from the Indian localities and their possible role in kala-azar transmission, the correct identification of sand flies becomes of significant value in the study of epidemiology of leishmaniases and other viral diseases. In the present paper, species of the subgenus Sintonius Nitzulescu are not only keyed and their distributional ranges are given but in order to facilitate zoologists and medical researchers, the morphology of diagnostic characters of S. clydei, especially mouth parts and male and female genitalia are studied, and results presented. In this light, their phylogenetic relationships are also briefly discussed.